KONSTRUKSI PANDANGAN CRITICAL LEGAL THEORY TENTANG THE RULE OF LAW, THE MEANING OF LAW, DAN THE LAW AND SOCIETY - Benediktus Hestu Cipto Handoyo (Arena Hukum, 2018)
AbstractParadigm between the theory of legal positivism and the flow of legal realism shows a difference. The two legal theory paradigms are used as an introduction in discussing Postmodern Legal Theory or called Critical Legal Theory, because the two theories above show the characteristics of Traditional Legal Theory, especially in looking at the rule of law, the meaning of law, and the law and society. The problem in this article is how is the Critical Legal Theory's view of legal concepts specifically related to the rule of law, the meaning of law, and the law and society? Is the statement as stated by Gary Saalman acceptable or not? And does postmodern legal theory do occur in legal reality in Indonesia? This article uses a normative juridical method and a comparison of legal theories through a philosophical approach. The results showed that deconstruction of the old legal theory and included in the postmodern framework in the field of law, although it seemed blindly and